2022
DOI: 10.1016/j.jaerosci.2021.105848
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of an aerosol extraction device for use in COVID-19 surgical tracheotomy

Abstract: In view of the ongoing COVID-19 pandemic and its effects on global health, understanding and accurately modelling the propagation of human biological aerosols has become crucial. Worldwide, health professionals have been one of the most affected demographics, representing approximately 20% of all cases in Spain, 10% in Italy and 4% in China and US. Methods to contain and remove potentially infected aerosols during Aerosol Generating Procedures (AGPs) near source offer advantages in reducing the contamination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…• Development of a tracheostomy robot prototype [31] • Design of other devices related to tracheostomy [32] • Development of robots for MISs [37], [39], [40] • Reviews of surgical robots [34], [36], [42] • Design specifications of surgical robots [33], [35], [38], [41], [43] A summary, including brief descriptions and requirements collected from each study, is shown in Table I. After synthesizing all the information, 36 potential design requirements were developed and listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…• Development of a tracheostomy robot prototype [31] • Design of other devices related to tracheostomy [32] • Development of robots for MISs [37], [39], [40] • Reviews of surgical robots [34], [36], [42] • Design specifications of surgical robots [33], [35], [38], [41], [43] A summary, including brief descriptions and requirements collected from each study, is shown in Table I. After synthesizing all the information, 36 potential design requirements were developed and listed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As for the recommendations on surgical procedures, these range from the selection of the anesthetic modality, the adequate manipulation of the airways, to the execution of the surgical technique ( 12 , 20 , 21 , 24 ) . In the context of the Covid-19 pandemic, the main objective is to reduce the production and dispersion of air particles as much as possible, opting for procedures that do not produce aerosols, gases or fumes ( 20 , 45 ) . Whenever possible, anesthesia through locoregional blocks should be used, considering that general anesthesia requires manipulation of the pathways, with ventilation maneuvers, tracheal intubation and, consequently, aerosol production ( 17 , 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations /CDC 2020/ English/US air particles as much as possible, opting for procedures that do not produce aerosols, gases or fumes (20,45) . Whenever possible, anesthesia through locoregional blocks should be used, considering that general anesthesia requires manipulation of the pathways, with ventilation maneuvers, tracheal intubation and, consequently, aerosol production (17)(18) .…”
Section: Interim Infection Prevention and Control Recommendations For...mentioning
confidence: 99%
“…Quanto às recomendações sobre os procedimentos cirúrgicos, estas vão desde a escolha da modalidade anestésica, a manipulação adequada de vias aéreas, até a execução da técnica cirúrgica (12,(20)(21)24) . No contexto da pandemia da Covid-19, o objetivo principal é reduzir ao máximo a produção e a dispersão de partículas aéreas, optando por procedimentos que não produzam aerossol, gases ou fumaças (20,45) . Sempre que possível, deve-se utilizar a anestesia por bloqueios locorregionais, considerando que a anestesia geral requer a manipulação de vias, com manobra de ventilação, intubação traqueal e consequentemente produção de aerossol (17)(18) .…”
Section: Recomendações Para O Ambiente Do Centro Cirúrgicounclassified